A Survey on Production Practices and Utilization of Vine Spinach (Basella sp.) In Western Kenya - J. , Oyugi; F. N W , Maina; M, Kamara .; K. N. 1, Rop (African Journal of Education,Science and Technology (AJEST), 2021)
Vine spinach is a traditional vegetable that is highly nutritious and a source of income in Kenya. It is semi domesticated and its potential to provide much needed nutrients at the household level is therefore curtailed. Its production is also constrained by varied agronomic practices, lack of quality seed for propagation, seed dormancy as well as its mucilaginous nature when cooked. A survey was conducted to obtain indigenous information on production and consumption of vine spinach. Purposive sampling was used select 77 farmers in Kakamega and Kisii counties for interviews using a pretested structured questionnaire. Data obtained was analyzed using descriptive statistics (percentages and means) from SPSS statistical package. It was found that majority of the farmers grew green leafed vine spinach (Basella alba), used vines to establish the plants, sourced the vines from their own farms, used organic but not inorganic fertilizers, used fences as a means of trelising the plants, did not observe any pests and diseases and harvested leaf once per week. Plant spacing and cooking methods varied considerably. Information obtained forms a basis for standardizing agronomic practices, provision of quality and nutritive ways preparing vine spinach for consumption.